2010
DOI: 10.1111/j.1095-8649.2010.02685.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, extinction risk and conservation of Malaysian fishes

Abstract: A total of 1951 species of freshwater and marine fishes belonging to 704 genera and 186 families are recorded in Malaysia. Almost half (48%) are currently threatened to some degree, while nearly one third (27%) mostly from the marine and coral habitats require urgent scientific studies to evaluate their status. Freshwater habitats encompass the highest percentage of threatened fish species (87%) followed by estuarine habitats (66%). Of the 32 species of highly threatened (HT) species, 16 are freshwater and 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 30 publications
(31 reference statements)
4
95
2
3
Order By: Relevance
“…The total number of fish species from the present study had higher than the previous studies (47 fish species) but lower than the total number of species recorded in the State of Perak (128 fish species) (Yusoff et al 2006;Chong et al 2010). Among all fish species, cyprinid fishes are the most dominant family in both lentic and lotic areas.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The total number of fish species from the present study had higher than the previous studies (47 fish species) but lower than the total number of species recorded in the State of Perak (128 fish species) (Yusoff et al 2006;Chong et al 2010). Among all fish species, cyprinid fishes are the most dominant family in both lentic and lotic areas.…”
Section: Discussioncontrasting
confidence: 47%
“…Among all fish species, cyprinid fishes are the most dominant family in both lentic and lotic areas. Many species belonging to this family are naturally found throughout tropical and subtropical of southern and southeastern Asia (Zakaria-Ismail 1994;Nguyen and De Silva 2006;Chong et al 2010). Twenty-two fish species recorded from previous surveys were frequently encountered in our surveys, but we did not encounter 29 of the previously reported species in our surveys, including the type locality of two species from this reservoir, Lepidocephalichthys furcatus and Macrognathus perakensis (de Beaufort 1933;Herre and Myers 1937).…”
Section: Discussionmentioning
confidence: 54%
“…Such declines are unsurprising in Malaysia, as a number of scientific studies have already highlighted similar problems. For example, Chong et al (2010) found that out of 1,951 species of freshwater and marine fish studied in Malaysia, nearly half are threatened to some degree. Chew and Zulkafli (2012) provided another view by accentuating the need for conservation efforts of species such as Jelawat (Leptobarbus hoevenii), Kelah (Tor tambroides) and Temoleh (P. Jullieni), as these species are now scarce.…”
Section: Alternative Income Sourcesmentioning
confidence: 99%
“…Most of 89 the class labels, synonyms and definitions in the FO correspond to those in the reference book. Some of 90 the terms for specimen entries are taken from experimental data such as sampling data provided by Chong 91 et al (Chong, Lee & Lau, 2010), while others are taken from public online entries such as Wikipedia 92 ("Wikipedia") and DBPedia (Heath & Bizer, 2011). 93 One of the most important aspects in ontology creation is consistency; hence, we sought to follow a 94 standard naming convention while creating the FO.…”
mentioning
confidence: 99%